Recurrence risk of occult micrometastases and isolated tumor cells in early stage endometrial cancer: A case control study - Tara Castellano; Lewis Hassell; Rachel Conrad; Conner S. Davey; Sunam Husain; Justin D. Dvorak; Kai Ding; Camille Gunderson Jackson (Elsevier, 2021)
Objectives: To determine whether previously undetected occult micrometastasis (MM) or isolated tumor cells (ITC) is associated with increased recurrence odds in stage I-II endometrioid adenocarcinoma. Methods: Women with recurrent stage I/II EC who had complete pelvic and para-aortic were identified as the outcome of interest. A case-control study was designed with the exposure defined as occult MM/ITC not seen on original nodal pathology. Controls were found by frequency-matching in a 1:2 case control ratio. Original nodal slides were re-reviewed, stained and tested with immunohistochemical to detect occult MM/ITC and the odds of associated recurrence was calculated. Results: Of 153 included, 50 with and 103 without recurrence, there was no difference in age (p = 0.46), race (p = 0.24), stage (p = 0.75), FIGO grade (p = 0.64), lymphovascular space invasion (LVSI); p = 1.00, or GOG 99 high-intermediate risk (HIR) criteria (p = 0.35). A total of 18 ITC (11.8%) and 3 MM (2.0%) not previously identified were found in 19 patients. Finding occult MM/ITC was not associated with more lymph nodes (LN) removed (p = 0.67) or tumor grade (p = 0.48) but was significantly associated with stage (p < 0.01). LVSI (p = 0.09) and meeting high-intermediate risk criteria (p = 0.09), were closely associated but not statistically significant. Isolated ITC were not associated with increased odds for recurrence (OR 0.71, CL: 0.20 - 2.22, p = 0.57), recurrence free survival (RFS) (p = 0.85) or overall survival (OS) (p = 0.92). Conclusions: In early-stage EC, identification of occult MM or ITC is uncommon and associated with stage. The presence of ITC was not associated with increased odds of recurrence. Adjusting stage or treatment may avoided based on ITC alone. Isolated MM were rare in our population, and further investigation is warranted.